A significant methane source over the Chukchi Sea shelf and its sources. (15th September 2017) - Li, Yuhong; Zhan, Liyang; Zhang, Jiexia; Chen, Liqi; Chen, Jianfang; Zhuang, Yanpei
Abstract: Dissolved methane (CH4 ) was measured at various depths in the western Arctic Ocean. The CH4 concentrations at the surface show an increasing trend northward toward stations at the shelf break and a decreasing trend toward stations in the Canada Basin. The mean sea-to-air flux is estimated to be 10.08 μmol/m 2 /d, indicates that the Chukchi Sea shelf (CSS) is an active site of CH4 . Methane concentrations at the shelf stations increase from the surface to the bottom, and the maximum nutrient concentrations occur in the bottom layer. Strong correlations exist between CH4 and PO4 3-, SiO4 2-, or NO2 -, suggesting that the production of CH4 is likely related to the degradation of organic matter in the sediment, supporting a biogenic source. At the slope and basin stations, the maximum values were observed in the subsurface of the upper halocline layer (UHL), and the concentrations decrease with increasing depth. The CH4 concentrations are elevated by ~ 7.9 nmol/L in the UHL compared with the homogeneous CH4 concentrations observed in the deep water. The elevated values in the UHL result primarily from northward spreading of CH4 -rich water from the shelf. A mass balance model was used to calculate the CH4 budget in the CSS. The results show that effluxes of CH4 from the sediment-water interface and the in situ production of CH4 represent the major sources of CH4 over the CSS (95%). The main outputs for CH4 in the CSS are the sea-to-air flux and oxidation of CH4 in the water column, which account for 95% of the CH4 exports. Highlights: CH4 in bottom of the CSS is related to the degradation of organic matter. Northward spreading of water contributes to the maxima of CH4 in the UHL. Sediment emission and sea-to-air flux are major source or sink of CH4 in the CSS.